Micro-geração de energia elétrica a partir de correntes de marés para sistemas isolados - SOUSA, Bruno Felipe Gomes de Sá (2018)
The most favorable sites for the exploitation of oceanic energies are characterized by high current intensities and average high tide height. In Brazil, the greatest amplitudes and speed of tides are in the north and northeast, in the states of Amapá, Pará and Maranhão. For example, the energy potential available on the coast of Maranhão was estimated at 22 TWh / year. In terms of tidal currents, the São Marcos Bay in Maranhão and the channel of Varador in Amapá should be highlighted. However, in Brazil does not yet have an inventory with the potential of tidal currents. This dissertation deals with the optimal sizing of a micro power plant based on tidal current. In order to ensure reliable power supply to the insulated system, an energy storage system must be taken into account. Considering the variation of the sea currents as well as the energy demand curve, the problem is formulated as a multi-period nonlinear optimization problem. The physical, environmental and economic constraints of the problem to be optimized are identified and formalized. To solve the problem it’s use a metaheuristic based on Genetic Algorithms. As a case study, it is considered a place located in the Bay of São Marcos (Maranhão), more specifically no channel on the island of Medo. Through the in situ data, the available energy potential curve is obtained. The analysis of the results leads to interesting conclusions that contribute to a better understanding of ocean energy and to strategies for better exploration of ocean energy.